Framing Europe : attitudes to European integration in Germany, Spain, and the United Kingdom - Díez Medrano, Juan (Princeton studies in cultural sociology., 2003)
"This book provides a major empirical analysis of differing attitudes to European integration in three of Europe's most important countries: Germany, Spain, and the United Kingdom. From its beginnings, the European Union has resounded with debate over whether to move toward a federal or intergovernmental system. However, Juan Diez Medrano argues that empirical analyses of support for integration - by specialists in international relations, comparative politics, and survey research - have failed to explain why some countries lean toward federalism whereas others lean toward intergovernmentalism."--Jacket.